The influence of a specially programmed functional training in improving the vertical jump of senior soccer players - Tasevski Zikica; Gontarev Serjoza; Markovski, Nebojsha; Ruzdija Kalach; Vuksanovikj, Vladimir (Research in Physical Education, Sport & Health, 2019)
A survey was conducted on a sample of 50 soccer players between 17 and 30 years of age, with the main goal to determine the quantitative transformational changes of the tests for vertical jump assessment, under the influence of a specially programmed functional training with top soccer players who play at different positions in the team. In order to accomplish the research objectives, three tests for vertical jump assessment were applied: squat jump (SJ), countermovement jump (CMJ), and countermovement jump with arm swing (CMJA). The experimental program was applied within a period of six working weeks with four trainings per week. The trainings were applied with a circular method of work, and the respondents were divided into groups, each of two players. The results of the study suggest that the six-week experimental training program of functional training positively affected the improvement of the average results in the three tests. On the basis of the numerical values of the arithmetic means and the percentage differences, one can conclude that during the period of six weeks, in the entire sample of respondents there was an improvement of 18.20% in the Squat Jump test, the improvement in the Countermovement Jump test was 8.99%, and in the Countermovement Jump With Arm Swing test an improvement of 18.59% was achieved.
Keywords: jumping; explosive power; measurement